The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijms20143423
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms: The Microbial “Protective Clothing” in Extreme Environments

Abstract: Microbial biofilms are communities of aggregated microbial cells embedded in a self-produced matrix of extracellular polymeric substances (EPS). Biofilms are recalcitrant to extreme environments, and can protect microorganisms from ultraviolet (UV) radiation, extreme temperature, extreme pH, high salinity, high pressure, poor nutrients, antibiotics, etc., by acting as “protective clothing”. In recent years, research works on biofilms have been mainly focused on biofilm-associated infections and strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
406
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(413 citation statements)
references
References 157 publications
4
406
0
3
Order By: Relevance
“…For example, in Deinococcus geothermalis, biofilm formation has been linked to an increased desiccation resistance, although it has also been linked to a decrease in UV resistance due to the photodissociation of water molecules retained in the EPS matrix, leading to increased ROS concentrations (Frösler et al ., 2017). On the other hand, biofilm structures have also been described to protect against UV‐radiation due to physical shading (Yin et al ., 2019). Interestingly, several bacterial taxa displayed very similar profiles throughout time, suggesting an interdependence between these genera.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Deinococcus geothermalis, biofilm formation has been linked to an increased desiccation resistance, although it has also been linked to a decrease in UV resistance due to the photodissociation of water molecules retained in the EPS matrix, leading to increased ROS concentrations (Frösler et al ., 2017). On the other hand, biofilm structures have also been described to protect against UV‐radiation due to physical shading (Yin et al ., 2019). Interestingly, several bacterial taxa displayed very similar profiles throughout time, suggesting an interdependence between these genera.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, of the 10 antibiotics tested, only gentamicin and ceftaroline were able to eradicate the biofilms. It has been reported that bacterial biofilms are also highly resistant to ultraviolet and heavy metals [ 54 ]. In addition to bacteria, fungi, especially Candida , are present in DFU biofilm-associated wound samples [ 55 ].…”
Section: Overview Of Biofilms In Dfumentioning
confidence: 99%
“…When a bacteria formed a biofilm, it promotes growth and survival, it becomes extremely difficult to be destroyed (Georgescu et al, 2016). Biofilm supports the colonization of bacteria, which is showing resistant to most antibiotics (Yin et al, 2019). Among bacterial pathogens, P. aeruginosa inherent resistance to antibiotics such as aminoglycosides, carbapenems, penicillins, ZANCO Journal of Pure and Applied Sciences 2020 quinolones and cephalosporins.…”
Section: Fritillaria Zagrica Stapf Is a Species Verymentioning
confidence: 99%